Perception, experience and relationship with food and eating in adults with cystic fibrosis. Issue 5 (16th December 2021) - Barrett, Joanne; Slatter, Georgina; Whitehouse, Joanna L.; Nash, Edward F.
Abstract: Background: Cystic fibrosis (CF) is a multisystem disorder that primarily affects the respiratory and gastrointestinal systems. Dietetic therapy is a prominent aspect of CF management, with patients receiving nutritional surveillance and advice throughout their lifetime. The present study aimed to explore the perception, experience and relationship with food and eating in adults with CF. Methods: Semi‐structured telephone interviews were conducted with nine adults with CF. Interviews were audio‐recorded, transcribed verbatim and analysed thematically following a previously described six‐phase procedure. Results: Six themes were identified: 'Sustained influence of eating experience in childhood', 'Eating for health: weight gain to prevent infection', 'Balancing health and body image', 'I'm different, ' 'Strategies for managing food intake' and 'Support from family, friends and the CF Team'. Participants talked about the range of strategies they employ, with a focus on eating well and choosing high calorie foods being an important part of their health management strategy. This is driven by the belief that a good weight ensures better health and perceiving eating as a treatment. Conclusions: This group felt able to cope well and had developed strategies to manage their dietary needs. Food experience was variable throughout their lifetime, with childhood experience having a sustained effect on adult eating behaviour. Weight gain, body image and dietary health implications are considerable concerns for patients. New CF transmembrane modulator treatments (CFTR modulators) are changing the dietary needs of this population. It is important that these issues are explored during dietetic consultations to identify barriers to dietary change. Abstract : Key points: Experience of eating and tube feeding during childhood had a sustained influence on the eating behaviours of adults with cystic fibrosis (CF). Food choice was influenced by body image, weight and health goals. Eating well and achieving a healthy weight was perceived as an important strategy to prevent respiratory infections and keep well. Dietetic consultations with adults with CF should explore historical food experience and body image goals to identify motivations and barriers to dietary change.